2019
DOI: 10.1177/2332858419857702
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Early Spelling Game: The Role of Auditory and Visual Support

Abstract: Adult-preschooler shared writing activities encourage children, through playful, meaningful activity, to analyze the sound structure of words and support phonemic segmentation and letter learning (Bingham & Mason, 2018; Gerde et al., 2012; Neumann & Neumann, 2014; Puranik & Lonigan, 2011). When practicing early writing/spelling, preschoolers frequently explore the sound-letter relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Digital media convey textual, auditory and visual information and Paivio (2014) posits that processing auditory and visual information enables high order learning as it supports processing of verbal and non-verbal information. Similarly, Elimelech and Aram (2019) have concluded that digital literacy games can improve and enhance young children's literacy at kindergarten. Empirical evidence from their study also revealed that an experimental group that used auditory and visual media scored higher on spellings compared to control group which had access to print.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital media convey textual, auditory and visual information and Paivio (2014) posits that processing auditory and visual information enables high order learning as it supports processing of verbal and non-verbal information. Similarly, Elimelech and Aram (2019) have concluded that digital literacy games can improve and enhance young children's literacy at kindergarten. Empirical evidence from their study also revealed that an experimental group that used auditory and visual media scored higher on spellings compared to control group which had access to print.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The different tests reveal that the evolution in the phonological awareness of the children who have participated in these experimental groups is not due only to the use of the computer, but also to the application of specific games and software aimed at improving their PA, with the accompaniment of a teacher for a specific period: 1 month (Elimelech & Aram, 2019), 3 months (Bus & Kegel, 2012), 5 months (Luna et al, 2018), 1 year (Guindera & Gil, 2017). According to the results given in these articles, specialists note significant differences in the level of learning that children achieve through this type of game, assisted by a teacher, while the evolution with the use of other technologies such as digital books (Elimelech & Aram, 2019) has been non-existent. Here, it is important to highlight that there is not enough certainty about the proper time to carry out an effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, we can affirm that more studies are needed to get a better perspective on the relationship between the pedagogical use of ICT and the development of phonological awareness and its different levels. Thus, in the same vein, it is important to explore the uses of technology and how it can facilitate early literacy instruction and development (Elimelech & Aram, 2019). Following these ideas, the main purpose of this theoretical review goes beyond establishing the state of the art; what is sought is to determine the strengths and weaknesses of the few researches that have been conducted so far and to understand what the prospects are for expanding this field of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have also shown that multimedia interactions, especially pictures with text, have been powerful in improving spelling performance and rates of vocabulary acquisition [45,60,73,68,20]. Vocabulary size is known to have valuable contributions towards better reading comprehension [16,1].…”
Section: Literacy Research Backgroundmentioning
confidence: 99%